Evaluation of facial pleasantness in patients with complete and unilateral cleft lip and palate rehabilitated and submitted to orofacial harmonization - Daniel Giaretta FANGUEIRO; Daniela Gamba GARIB; Ana Cláudia de Castro Ferreira CONTI; Lucila LARGURA (Dental Press Editora, 2024)
ABSTRACT Objective: The objective of the present prospective case control study was to evaluate the facial pleasantness of patients with complete and unilateral cleft lip and palate at the end of interdisciplinary rehabilitation, submitted to facial fillers based on hyaluronic acid. Methods: The study group consisted of 18 individuals with complete unilateral cleft lip and palate, aged between 18 and 40 years (mean age 29 years) of both sexes. The patients presented a concave profile with mild to moderate maxillary deficiency, with completed orthodontic treatment and conducted by means of dentoalveolar compensations without orthognathic surgery. Participants underwent facial filling procedures with hyaluronic acid (HA) in the midface, inserted by a single operator. Standard photographs in frontal norm at rest, right profile at rest, and left profile at rest were obtained from each patient at the following operative times: (T1) pre-filler and (T2) and one-month post-filler. The photographs in T1 and T2 were randomly placed on a page of a virtual album. A 5-point Likert scale was used to assess facial pleasantness. The photographs were evaluated by two groups of evaluators consisting of 18 individuals with cleft lip and palate (CLPG=18) and 18 orthodontists with experience in the treatment of clefts (OG=18). For comparison between phases T1 and T2, and between evaluators with orofacial clefts and orthodontists, the Wilcoxon test was used (p<0,05). Results: People with cleft lip and palate rated their face as more pleasant after the midface filling procedure. In the perception of the orthodontists, on the other hand, the facial pleasantness remained similar after the facial filling procedure. Conclusions: The filling of the middle third of the face in patients with cleft lip and palate treated without orthognathic surgery increased the pleasantness of the face in the opinion of laypeople with cleft lip and palate.